2018
DOI: 10.3389/fmicb.2017.02622
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of the Flying Squirrel's Cecal Microbiota under a Leaf-Based Diet, Based on Multiple Meta-Omic Profiling

Abstract: Mammalian herbivores rely on microbial activities in an expanded gut chamber to convert plant biomass into absorbable nutrients. Distinct from ruminants, small herbivores typically have a simple stomach but an enlarged cecum to harbor symbiotic microbes; however, knowledge of this specialized gut structure and characteristics of its microbial contents is limited. Here, we used leaf-eating flying squirrels as a model to explore functional characteristics of the cecal microbiota adapted to a high-fiber, toxin-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…These authors commented that changes to the metatranscriptome can be identified earlier than changes to the microbial community itself and may be useful as a tool for predicting impending change to the community composition ( Hatton et al , 2017 ). Metatranscriptomic analysis was also cited as an ideal next step in a study characterizing the caecal microbiome of flying squirrels and would be interesting to employ in future studies on the prairie dog microbiome ( Lu et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors commented that changes to the metatranscriptome can be identified earlier than changes to the microbial community itself and may be useful as a tool for predicting impending change to the community composition ( Hatton et al , 2017 ). Metatranscriptomic analysis was also cited as an ideal next step in a study characterizing the caecal microbiome of flying squirrels and would be interesting to employ in future studies on the prairie dog microbiome ( Lu et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes/firmicutes ratio may be related to gut microbiota and host metabolism relationships. Regarding the Bacteroidetes to Firmicutes ratio of gut microbiota, increased Firmicutes was associated with obesity in a laboratory mouse model and humans 55,56,71 ; however, wild animals, especially herbivorous mammals, harbor much more Firmicutes than Bacteroidetes [72][73][74] . For strictly leaf-based diet cases, folivorous mammals can be either foregut-or hindgut-fermenters, with distinct strategies to degrade a high-fiber diet 9 , thereby contributing to unique gut microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…We found clear distinctions in faecal microbial communities, particularly for bacteria, among Dipodomys species (Figures S3–S11; Tables S2 and S3). Recent work has correlated changes in gut microbial diversity and activity to seasonal dietary shifts in wild black howler monkeys ( Alouatta pigra ; Amato et al, 2015) and plateau pika ( Ochotona curzoniae ; Wang et al, 2020), and advances in genomic sequencing and metabolite profiling now allow for direct comparisons between gut microbial community composition, gut microbial activity and host digestive environment (Lu et al, 2018). Our study demonstrates the utility of AA δ 13 C and δ 15 N analysis in connecting host nutrient acquisition to gut microbial activity and provides preliminary evidence of seasonal variation in the proportional contributions of gut microbiota as AA ESS sources in Dipodomys (Figure S14; Table S10).…”
Section: Discussionmentioning
confidence: 99%